Atoms in electromagnetic fields - Cohen-Tannoudji, Claude, 1933- (World Scientific series on atomic, molecular, and optical physics ;, 2004)
This invaluable book presents papers written during the last 40 years by Claude Cohen-Tannoudji and his collaborators on various physical effects which can be observed on atoms interacting with electromagnetic fields. It consists of a personal selection of review papers, lectures given at schools, as well as original experimental and theoretical papers. Emphasis is placed on physical mechanisms and on general approaches (such as the dressed atom approach) having a wide range of applications. Various topics are discussed, such as atoms in intense laser fields, photon correlations, quantum jumps.